RETIREMENT AND QUALITY OF LIFE IN SENIORS - Alpízar Jiménez, Idalia (2011)
Interest in retirement is on the increase, especially given the rapid demographic changes and increasing life expectancy. Retirement is a process that requires a comprehensive approach and gerontological intervention. Since it is associated with old age it often implies a threat, particularly for those who have made work their source of identity. The impact of the transition from an active stage to a less active period may trigger some conditions that may be detrimental to the individual´s physical and emotional health. This happens because retirees have not undergone the appropriate retirement preparation and adaptation processes. Adaptation is therefore essential for retirement to be pleasant and for the retiree to enjoy a higher quality of life. Consequently, it is pertinent that all entities have programs aimed at providing proper orientation for the retirement process. In particular, the National University of Costa Rica has not implemented proper guidelines to address the retirees´ situation. Although actions have been taken on some occasions, they have not been followed up on. Within this context, it makes sense to have a retirement adaptation program designed to include gerontological aspects in the National University retirement process. From a holistic point of view, intervention contributes to a better acceptance of old age and its accompanying transitions, which are characterized by a series of losses, mainly including the loss of the employment role and status.